Understanding Ḥadīth, “Father of Prophet Muḥammad in Hell” In Shabir Ally's Perspective - Mohamad Zakky Ubaid Ermawan; Nasrulloh Nasrulloh; Mohammad Fadil Akbar Islamy (Yayasan Pesantren Mahasiswa An-Nur, 2023)
Shabir Ally is a Canadian Islamic preacher and apologist. He was interviewed on a YouTube channel named ‘Let The Quran Speak’ about the prophet’s father in hell. However, his explanation is only a brief explanation. Meanwhile, understanding the Ḥadīth of the Prophet Muḥammad Ṣallallahu ‘Alayhi Wa Sallam. Must also use the methodology of Ḥadīth knowledge and the opinions of experts about the true meaning contained in the Ḥadīth. This article aims to provide a more complete explanation of what has been explained by Dr. Shabir Ally in his interview session. This research is a type of literature review research. The result of this article can be summarized as follows: Shabir Ally is in the middle position, neither saying the Prophet's father was in hell nor saying the Prophet's father was saved from the torment of hell. Moreover, the words of the prophet who said, 'My father is also in hell,' are just additions to the story by the people who told that event. However, the author(s) have not found the primary basis for Shabir Ally to say that so far.